Effects of a therapeutic exercise program in children with non-cystic fibrosis bronchiectasis: A pilot randomized controlled trial - Joschtel, Barbara; Gomersall, Sjaan R.; Tweedy, Sean; Petsky, Helen; Chang, Anne B.; Trost, Stewart G. (Frontiers in Pediatrics, 2022)
Background In the absence of randomized controlled trials (RCTs) on the benefits of therapeutic exercise programs involving children with bronchiectasis, we undertook a pilot RCT to evaluate the effects of a play-based therapeutic exercise program on fundamental movement skill (FMS) proficiency. The effects of the program on cardiorespiratory fitness, perceived competence, and health-related quality of life (HR-QoL) were examined as secondary outcomes. Methods Children [median (IQR) age: 6.8 (5.3–8.8) years] with bronchiectasis unrelated to cystic fibrosis were randomized to a 7-week therapeutic exercise program (n = 11) or wait-list control (n = 10). The exercise program comprised 7 × 60-min weekly sessions and was supplemented by a home-based program 2-days/week. Participants were assessed on: FMS (locomotor and object control skills) using the Test of Gross Motor Development 2nd Edition (TGMD-2); cardiovascular fitness by calculating the percent change in heart rate (%ΔHR) from rest to completion of the first stage of a submaximal treadmill test; perceived competence using Harter’s athletic competence subscale; and QoL with the PedsQL. Results Significant group by time interactions were observed for locomotor and object control skills. Children completing the therapeutic exercise program exhibited significant improvements in both locomotor (pre 29.0 ± 2.0, post 35.2 ± 2.2, p = 0.01) and object control (pre 27.0 ± 2.0, post 35.5 ± 2.2, p = 0.01) skills, with no significant change in controls (pre 31.6 ± 2.1, post 31.8 ± 2.3 and pre 31.0 ± 2.1, post 32.3 ± 2.3, respectively). Among children completing the program, %ΔHR declined by 6% points, while %ΔHR declined only marginally among controls (0.9% points), but the group by time interaction was not statistically significant. The program had a small positive impact on competence perceptions (Cohen’s d = 0.2) and HR-QoL (Cohen’s d = 0.3). Conclusion This pilot RCT provides preliminary evidence for the efficacy of a play-based therapeutic exercise program to improve proficiency in FMS and fitness in children with bronchiectasis. The results are sufficiently positive to warrant conducting a larger RCT testing the efficacy of the exercise program in children with bronchiectasis and/or other chronic respiratory conditions.